Profiling Younger Adults' Communication About Aging. Issue 2 (14th March 2016) - Gasiorek, Jessica; Fowler, Craig
Abstract : According to the Communicative Ecology Model of Successful Aging (CEMSA), how people talk about age can have implications for how they cope with aging later in life. However, most research on communication and successful aging has focused on older adults. In this study, we use latent class analysis to profile how younger adults (age 18–39) communicate about aging and examine how these profiles relate to their attitudes toward aging (affect, efficacy, anxiety, and perceptions of successful aging). Consistent with past research on older adults, we found three distinct profiles of communication behavior ( disengaged, engaged, and bantering ). An engaged profile was clearly associated with the most positive attitudes toward aging, while a disengaged profile was associated with the least positive attitudes. These findings suggest that patterns of talk about aging may start early in life, underscoring the importance of studying communication about aging across the lifespan.